Satellites, oceanography, and society - Halpern, David, 1942- (Elsevier, 2000)
The book shows how the new observations from satellites required advances in theory and influenced societal decision-making. Chapters have a review with an extensive reference list, making the book an excellent source of information for biological and physical oceanographers and atmospheric scientists. A large range of state-of-the art applications of satellite data (altimeter, color, infrared radiometer, scatterometer, synthetic aperture radar) visible in regional-to-global scale ocean studies integrating satellite and in-situ measurements with circulation models are covered in the book. Subjects include forecasting of surface waves, both swell and windsea, and surface wind; El Niño/La Niña; exchange of water masses between ocean basins, Rossby waves; eddies and filaments; fisheries; coastal ocean dynamics; phytoplankton dynamics; and ideas to measure sea surface salinity.
Keywords: Oceanography -- Remote sensing -- Congresses.; Astronautics in oceanography -- Congresses.; elektronické knihy; electronic books